Identification of a Drosophila melanogaster glutamate-gated chloride channel sensitive to the antiparasitic agent avermectin. - Cully, D.F.; Paress, P.S.; Liu, K.K.; Schaeffer, J.M.; Arena, J.P. (Journal of Biological Chemistry, 1996)
Glutamate-gated chloride channels, members of the ligand-gated ion channel superfamily, have been shown in nematodes and in insects to be a target of the antiparasitic agent avermectin. Two subunits of the Caenorhabditis elegans glutamate-gated chloride channel have been cloned: GluCl-alpha and GluCl-beta. We report the cloning of a Drosophila melanogaster glutamate-gated chloride channel, DrosGluCl-alpha, which shares 48% amino acid and 60% nucleotide identity with the C. elegans GluCl channels. Expression of DrosGluCl-alpha in Xenopus oocytes produces a homomeric chloride channel that is gated by both glutamate and avermectin. The DrosGluCl-alpha channel has several unique characteristics not observed in C. elegans GluCl: dual gating by avermectin and glutamate, a rapidly desensitizing glutamate response, and a lack of potentiation of the glutamate response by avermectin. The pharmacological data support the hypothesis that the DrosGluCl-alpha channel represents the arthropod H-receptor and an important target for the avermectin class of insecticides.